Effect of Pre-treatment Processes to Ferulic Acid Extraction from Banana Stem Waste - N., Zainol; N., Masngut; S. N., Ismail (Universiti Putra Malaysia, 2016)
The present of ferulic acid (FA) in plants attract the attention of many researchers, especially in food, pharmaceutical and cosmetic industries. Banana stem waste (BSW) was generated from banana plantation. In this study, FA was extracted from BSW by using sugarcane press machine. Effect of two pre-treatment processes to ferulic acid extraction were studied namely the ultraviolet (UV) light pre-treatment and heating of BSW before extraction. Response surface method was utilized to construct the experimental table and to analyze the influences of both pre-treatment processes. The selected ranges for both pre-treatment processes were as follows : UV light (with or without) and heating temperature (25oC-90oC). The FA was analyzed by using high performance liquid chromatography (HPLC) and FA yield ranging from 0.0010mg/g to 0.1204 mg/g. The analysis of the results showed that heating BSW before extraction increased the ferulic acid yield however UV light pre-treatment did not give significant effect to ferulic acid extraction.